A influência das redes sociais na transferência de conhecimento em incubadoras de empresas de base tecnológica - Maria Gabriela de Cássia Miranda (2016)
This research identified and examined how the characteristics of social networks affect the sharing of tacit knowledge from the perspective of socialization Nonaka (1991), incubators of technology-based companies linked to universities in the state of Minas Gerais. Thus, we carried out a survey and semi-structured interviews to survey the attributes of social networks established between the internal members of the incubators and to understand the key sharing practices of tacit knowledge. We studied six incubators of technology-based companies, totaling 52 respondents, each social network analyzed separately. The results indicate that the incubators have different formations as the internal arrangement of the members as well as the employment of each. However, all studied incubators have dense and low degree of fragmentation social networks. What is a high degree of contact, high proximity between members, close ties and high levels of trust in co-workers, such factors contribute to the sharing of tacit knowledge in this environment. Finally, it was found that tacit knowledge sharing level depends directly on the contact degree and the level of trust between the internal members of business incubators. Already, the level of trust among members of the proximity to the network of actors and intensity of ties established between them. The main limitations of this study are related to difficulties in access to incubators because of the many demands that these are submitted. It should be noted also the implementation of CERNE methodology, high investments from the public and private power in innovation projects has demanded greater dedication of the incubators. At the same time, the few, the uncertainty of continuity by grants cuts of grants and fellowships organs. It is recommended for future work studying the clicks of social networks of incubators to understand the dynamics of each click and its relationship with other clicks for sharing tacit knowledge. In addition, it is considered relevant to the study of social networks, trust and sharing of tacit knowledge in more competitive environments to understand the difference of relations in these environments